1995
DOI: 10.1111/j.1365-2621.1995.tb06231.x
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and Sensory Properties of Dehydrated Bean Paste Products as Related to Bean Varieties

Abstract: The objective was to compare physicochemical properties of bean paste products from six bean varieties to determine whether there were significant differences in the resulting product. Crude protein in the dried bean pastes ranged from 23% to-29% and ash 1.1% to 1.8%. Fiber ranged from 16% to 6.3% soluble. 10.6% to 22.7% insoluble. and 12.3% to 28.3% total dietary fiber. No&arch polysaccharide contents varied from 12% to 32%. Only 7.5% to 13.8% of total raflinose and stachyose were retained in the paste produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
8
2

Year Published

1998
1998
2020
2020

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 11 publications
8
8
2
Order By: Relevance
“…The IDF fraction in raw beans and chickpeas formed the majority of the TDF, ranging from 64.1% to 94.4%. These results are close to that reported by Su and Chang (1995) who reported that the IDF fraction in raw dry beans was 72-90% of the TDF. Wang et al (2008) observed that IDF represented from 88.6% to 90.2% of the TDF in field peas.…”
Section: Effect Of Cooking On Proximate Compositionsupporting
confidence: 95%
“…The IDF fraction in raw beans and chickpeas formed the majority of the TDF, ranging from 64.1% to 94.4%. These results are close to that reported by Su and Chang (1995) who reported that the IDF fraction in raw dry beans was 72-90% of the TDF. Wang et al (2008) observed that IDF represented from 88.6% to 90.2% of the TDF in field peas.…”
Section: Effect Of Cooking On Proximate Compositionsupporting
confidence: 95%
“…In the present study, the cooking process brought about greater reductions in the levels of sucrose than those previously reported (Vidal-Valverde et al, 1998; Sá nchez- Mata et al, 1999;Martín-Cabrejas et al, 2003. During the cooking process the decreases in the levels of raffinose and stachyose, as flatulence-inducing sugars, might be attributed to heat hydrolysis to disaccharides and also to monosaccharides, or to the formation of other compounds (Su and Chang, 1995). Total available carbohydrates, considered as the sum of monosaccharides, disaccharides and available starch, increased in cooked legumes, while non-available carbohydrates decreased.…”
Section: Resultscontrasting
confidence: 76%
“…Comparing the studied legumes, it could be observed that white bean showed the highest level of TDF, followed by pink-mottled cream bean and chickpea, which both exhibited similar contents. As it has been reported (Li et al, 2002;Su and Chang, 1995;Mahadevamma and Tharanathan, 2004), IDF was the main fraction, which represented 75-96% of the TDF for the studied legumes. With respect to SDF, the contents of this fraction were noticeably different depending on the legume species, and the bean samples exhibited larger SDF fractions (25-22% of TDF) than did chickpea (4%).…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…The yields of bean paste ranged from 594-686 g/kg (18). The starch contents of raw bean ranged from 340-450 g/kg ( Table 1), lower than the values (510-530 g/kg in navy, pinto, faba, lentil, and mung beans) reported by Naivikul (19) and (560 g/kg in Adzuki beans) by Tjahjadi and Breene (7).…”
Section: Starch Content In Raw Beans and Bean Pastecontrasting
confidence: 51%